The Determining Taxpayer Compliance Factors from Online Game Top Up Using the Technology Acceptance Model (TAM) Approach - Razaq, Zihni Hashfi; Inayati, Nur Isna; Kusbandiyah, Ani; Mudjiyanti, Rina (Magister Akuntansi Universitas Pancasila, 2024)
Purpose: This research aims to assess the impact of understanding the determinants of taxpayer compliance using online game top-ups using the technology acceptance model (TAM) approach. Methodology: In this study, the data were collected by distributing questionnaires to 104 respondents, namely online game players who had ever topped up. Apart from that, respondents from the public were aged 20 years and over, playing online games, and regularly topped up games. The primary data used was obtained from the questionnaire. Finding: The results concluded that the perception of taxpayer convenience and the perception of taxpayer usefulness have a positive influence on taxpayer compliance. Meanwhile, taxpayer attitudes do not affect taxpayer compliance. Implication: The government can use the research results to formulate more effective tax policies for online game top-up transactions—for example, more explicit policies regarding tax rates and how to report them.The gaming industry can increase user confidence in their services with transparency and compliance with tax regulations. This research is expected to raise awareness of online game users' tax obligations, especially in digital transactions such as game top-ups. Originality: This research specifically examines tax compliance in the context of the Hoyoverse online game top-up, a relatively new and underexplored area in the tax literature. Originality also lies in the data collection methods which may involve surveys or interviews with online game users. Empirical data obtained from involved in online game top-ups provide strong validity to the research findings.